Health Belief Model Predictors of Tertiary Preventive Behavior and HbA1c Levels among Patients with Type 2 Diabetes Mellitus - Anindya Wahyu Utami; Dono Indarto; Erindra Budi Cahyanto; Vitri Widyaningsih; Eti Poncorini Pamungkasari; Bhisma Murti (Journal of Epidemiology and Public Health, 2026)
Background: Type 2 diabetes mellitus (T2DM) remains a major public health challenge worldwide. This study applied the Health Belief Model (HBM) to examine its association with tertiary preventive behavior and HbA1c levels among patients with T2DM. The study aimed to analyze the effects of HBM constructs on tertiary preventive behavior and their impact on HbA1c levels in patients with T2DM. Subjects and Method: A quantitative study with a cross-sectional design was conducted among 210 patients with T2DM receiving outpatient care at UNS Hospital. Data were collected between September and October 2025. The independent variables included perceived susceptibility, perceived severity, perceived benefits, self-efficacy, and cues to action. The dependent variables were tertiary preventive behavior and HbA1c levels. Data were analyzed using univariate analysis, bivariate analysis with simple logistic regression, and multivariate analysis using path analysis in STATA 13. Results: Self-efficacy (b = 0.190; 95% CI = 0.029 to 0.350; p = 0.020), perceived benefits (b = 0.162; 95% CI = 0.021 to 0.301; p = 0.023), and cues to action (b = 0.294; 95% CI = 0.122 to 0.465; p = 0.001) had direct and significant effects on tertiary preventive behavior. Tertiary preventive behavior (b = −0.183; 95% CI = −0.307 to −0.085; p = 0.004), age (b = 0.134; 95% CI = 0.005 to 0.263; p = 0.041), duration of diabetes (b = 0.164; 95% CI = 0.035 to 0.295; p = 0.014), and family history of diabetes (b = 0.228; 95% CI = 0.104 to 0.351; p < 0.001) had direct and significant effects on HbA1c levels. Sex had direct but non-significant effects on both tertiary preventive behavior and HbA1c levels. Perceived susceptibility and perceived severity exerted indirect but significant effects on tertiary preventive behavior through perceived benefits. Conclusion: Self-efficacy, perceived benefits, cues to action, and sex directly influenced tertiary preventive behavior, whereas perceived susceptibility and perceived severity exerted indirect effects through perceived benefits. Furthermore, tertiary preventive behavior, duration of diabetes, age, family history of diabetes, and sex directly affected HbA1c levels.